Impact of Prolonged Electrochemical Cycling on Health Indicators of Aged Lithium-Ion Batteries for a Second-Life Use - Emanuele Michelini; Patrick Hoschele; Christian Ellersdorfer; Jorg Moser (IEEE Access)
The rising adoption of Electric Vehicles (EVs) is anticipated to significantly increase the number of used batteries entering the market. Repurposing these batteries for second-life applications is a promising solution that is technically, environmentally, and economically beneficial. However, the challenge lies in the uncertainty regarding the degradation mechanisms that these batteries have undergone during their first life, raising concerns about their safety for second-life usage. This study investigates the evolution of key Health Indicators (HIs) in automotive lithium-ion batteries to forecast critical conditions, such as aging capacity “knee” or sudden temperature spikes. Differently aged commercial 50 Ah NMC cells were tested by analyzing changes in several HIs, including State of Health (SOH), Coulombic efficiency, Voltage Relaxation Profile (VRP), and Open Circuit Voltage (OCV), over prolonged electrochemical cycling. This cycling process involves repeatedly fully charging and discharging the cells over a defined number of cycles. First, parallel aging (PA) is performed, in which each pair of cells is connected in parallel and cycled 100 times. Subsequently, single aging (SA) is performed, where each cell is cycled individually 100 times. The HIs are measured at three different stages: before PA, after PA, and after SA. Results indicated significant degradation, particularly in one of the cells, highlighting the variability in aging even among cells with similar aging histories. Changes emerged in all investigated HIs suggesting that prolonged electrochemical cycling led to Loss of Active Material (LAM) and Loss of Lithium Inventory (LLI), side reaction upon charging increase, and ion-accumulation. The findings underscore the necessity of employing multiple HIs beyond SOH to assess battery safety and performance accurately. Additionally, establishing “safety margins” based on these indicators can enhance battery monitoring strategies, ensuring reliability and safety in second-life applications.